Assisted suicide within long-term care facilities for older adults: organizational issues and processes experienced by health and social care providers in Switzerland - Castelli Dransart, Dolores Angela; Pedrazzini Scozzari, Elena (Frontiers in Psychiatry, 2025)
IntroductionAssisted suicide is still a controversial issue among health and social care providers. They are likely to face challenges in end-of-life care in long-term facilities for older adults, both on organizational and professional levels. Although Swiss professionals are not involved in the final act, they are involved to various extents in the process which leads to the death.MethodsThis qualitative study was carried out in 12 facilities in French-speaking Switzerland, which had been faced with requests for suicide assistance from older adults. A total of 36 professionals (physicians, nurses, nursing assistants, social workers, directors) were interviewed. Data were analyzed according to Grounded Theory principles.ResultsThe results uniquely describe how the process unfolds within facilities, from the initial request for suicide assistance to the aftermath of death. This process gives rise to many questions concerning the most appropriate ethical, professional and organizational way to respond to the requests and provide specific support to the requesting person, their family, and staff within the institution. Institutional life and daily operations are significantly impacted. Major adjustments are required to procedures, usual care routines, resource allocation and communication management within the facility. Institutions that set out a clear framework for the way in which the request is handled and provide sufficient and appropriate support for staff are the least disrupted, not only in terms of their operations, but also in terms of cohesion within teams and relationships between care teams and management.Throughout the process, communication within the institution is fundamental to enable staff members to find their bearings and make sense of the situation.DiscussionSeveral cross-cutting issues are identified: the need to strike a balance between respecting the procedures laid down by law or the directives of professional associations, and the need to open up spaces for exchange and the construction of meaning for those involved in the process. Further issues include the preparation and training of professionals, and the support provided to them throughout the process. Training and support seem critical to maintaining the continuity and quality of care, motivation and the health of staff.